Evolution of Islamic Calligraphy as an Extension of Art and Design in Pakistan (Al-Qamar, 2025)
Art represents the creative dimension of a society and design is the sense of formal organization that focuses functionality. In a society, art and design plays significant role being representative of its norms, culture, believes, traditions, and socio-political setting. These are the two progressive domains that allows freedom of expression which serve as the foundation of Islamic calligraphy in Pakistan. Although they have been questioned at different time periods but they kept on evolving besides external or internal constraints. Calligraphy is an art of beautiful writing that swiftly influences the sensations of a spectator. It is one such expression which has been celebrated immensely as an extension of art and design in the Islamic tradition that provides it prospering conditions for artistic evolution. In Pakistan, two of its school of thoughts exists: traditional calligraphy and modern calligraphy. In art, modern calligraphy is practiced with liberal approach. Some artists focused on its didactic gesture whereas some explored creative execution of the text beyond conventional means and the rest utilized it according to the consumerist approach. In communication design, calligraphy as typography plays essential role. It is used for purpose-based communication by dragging the attention of spectators towards a certain message. By means of artistic execution, manipulation of calligraphic text has taken the form of an art movement that appreciates its inclination towards the Islamic identity of the country. In Pakistan, practice of this genre is conceived as an integral part of the religious faith that ensures Divine blessings. As an art form, besides artists, designers have also contributed in finding innovative vistas for the creative execution of calligraphy. Both have used calligraphy as a tool of creative expression coupled with religious symbolism. Artistic manipulation of calligraphy has left strong influence on the development of text-based contemporary art of Pakistan as well.
Keywords: Traditional Calligraphy; Modern Calligraphy; Art and Design; Pakistani Art; Symbolism